Prediction of Polycyclic Aromatic Hydrocarbon Bioaccessibility to Earthworms in Spiked Soils by Composite Extraction with Hydroxypropyl-β-Cyclodextrin and Organic Acids - Zhang, Yanan; Yang, Xinglun; Gu, Chenggang; Bian, Yongrong; Liu, Zongtang; Jia, Mingyun; Wang, Fang; Wang, Daizhang; Jiang, Xin (Pedosphere, 2017)
Traditional exhaustive extraction methods often overestimate the risk of polycyclic aromatic hydrocarbon （PAH） bioaccessibility to biota. Therefore, reliable assessment methods need to be established. In this study, a composite extraction with hydroxypropyl- β-cyclodextrin （HPCD） and three low-molecular-weight organic acids, oxalic acid （OA）, malic acid （MA）, and citric acid （CA）, was used to predict the PAH bioaccessibility to earthworms, subjecting to two soils （red soil and yellow soil） spiked with selected PAHs, phenanthrene, pyrene, chrysene, benzo（a）anthracene, benzo（b）fluoranthene, benzo（k）fluoranthene, and benzo（a）pyrene. For both soils, concentrations of PAHs by composite extraction using HPCD-OA （R2 = 0.89-0.92, slope ： 1.89-2.03; n = 35）, HPCD-MA （R2 = 0.92-0.96, slope = 1.43-1.67; n = 35）, and HPCD-CA （R2 = 0.92-0.96, slope = 1.26-1.56; n = 35） were significantly correlated with PAH accumulation in the Eisenia fetida earthworms. Moreover, the HPCD-CA- and HPCD-MA-extracted PAH concentrations were closer to the earthworm-accumulated PAH concentration than the extraction using just HPCD. The results indicated that the composite extraction could improve the prediction of PAH bioaccessibility, and therefore can serve as a reliable chemical method to predict PAH bioaccessibility to earthworms in contaminated soils.